2019
DOI: 10.1039/c8ta12354c
|View full text |Cite
|
Sign up to set email alerts
|

Wearable binary cooperative polypyrrole nanofilms for chemical mapping on skin

Abstract: Wearable polypyrrole nanofilm arrays have been developed to extend the natural capabilities of the skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…As one of the most common semiconducting polymers, polypyrrole (PPy) exhibits characteristics that have been essential for novel organic and molecular electronics. Apart from low-cost synthesis, the use of PPy-based materials is quite promising due to their high energy-storage capacity, good electrical conductivity, and environmental stability . PPy structures can be synthesized as thin films, either chemically or electrochemically.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most common semiconducting polymers, polypyrrole (PPy) exhibits characteristics that have been essential for novel organic and molecular electronics. Apart from low-cost synthesis, the use of PPy-based materials is quite promising due to their high energy-storage capacity, good electrical conductivity, and environmental stability . PPy structures can be synthesized as thin films, either chemically or electrochemically.…”
Section: Introductionmentioning
confidence: 99%
“…The peaks at 400.3 and 401.6 eV were assigned to the positively charged polaron (41% of the total N content) and bipolaron (3.5% of the total N content) species, respectively (Figure S9). 74,75 The protonation of PPy is caused by oxidation during the polymerization process, which may generate positive charged polarons/bipolarons. 76 The XPS results confirm the formation of PPy, in which the polaron and bipolaron species can adsorb I 3…”
Section: Resultsmentioning
confidence: 99%
“…The IR spectra of C–O and C=O indicated that the skin and core of carbon fibers were not pyrolyzed homogenously. AFM-IR techniques have also been used to detect the polypyrrole wearable nanofilm devices on the surface of cellulose-based substrates [ 69 ].…”
Section: Afm-ir and Ir S-snom Application In Cellulose Materialsmentioning
confidence: 99%